Exploring risk transfer of human brucellosis in the context of livestock agriculture transition: A case study in Shaanxi, China - An, Cuihong; Shen, Li; Sun, Minghao; Sun, Yangxin; Fan, Suoping; Zhao, Chenxi; Nie, Shoumin; Luo, Boyan; Fu, Ting; Liu, Kun; Shao, Zhongjun; Chang, WenHui (Frontiers in Public Health, 2023)
With the booming of worldwide agriculture intensification, brucellosis, one of the most neglected zoonotic diseases, has become an increasing challenge for global public health. Although the transmission patterns of human brucellosis (HB) have been studied in many regions, the dynamic transfer processes of risk and its driving factors remain poorly understood, especially in the context of agricultural intensification. This study attempted to explore the risk transfer of HB between the exact epidemic areas and the neighboring or distant low-risk areas to explain the impact of livestock agriculture intensification and foodborne infections on the transmission of HB in Shaanxi Province as a case study. We adopted multiple approaches, including test-based methods, model-based methods, and a geographical detector to detect the spatial-temporal dynamic changes of high-risk epidemic areas of HB at the county scale. We also quantitatively estimated how the related factors drove the risk transfer of the disease. Results confirmed the risk transfer pattern of HB with an expansion from north to south in Shaanxi Province and identified two primary transfer routes. In particular, in the traditional epidemic areas of the Shaanbei plateau, the farm agglomeration effect can significantly increase the risk of HB. Meanwhile, retail outlets for milk and dairy products were partially responsible for the foodborne infections of HB in the emerging epidemic areas of Xi'an. This study not only contributed helpful insights to support HB control and prevention in the rapid transition of livestock agriculture but also provided possible directions for further research on foodborne HB infections in urbanized areas.